The osteogenic cell surface marker BRIL/IFITM5 is dispensable for bone development and homeostasis in mice. - Alexa Patoine; Abdallah Husseini; Bahar Kasaai; Marie-Hélène Gaumond; Pierre Moffatt (PLoS ONE)
BRIL (bone-restricted IFITM-like), is a short transmembrane protein expressed almost exclusively in osteoblasts. Although much is known about its bone-restricted gene expression pattern and protein biochemical and topological features, little information is available for BRIL physiological function. Two autosomal dominant forms of osteogenesis imperfecta (OI) are caused by distinct, but recurrent mutations in the BRIL gene. Yet, the underlying mechanisms by which those mutations lead to OI are still poorly understood. A previous report indicated that BRIL knockout (KO) mice had bone deformities, shortened long bones, and reproductive problems. Here we generated and systematically analyzed the skeletal phenotype of a new global Bril KO/LacZ knockin mouse model. KO mice reproduced and thrived normally up to 12 month of age. The skeletal phenotype of KO and WT littermates was assessed at embryonic (E13.5 to E18.5) and postnatal (2 days, 3 weeks, 3 months and 8 months) time-points. Embryos from E13.5 through to E18.5 showed significant X-Gal staining in all skeletal elements without any apparent patterning anomalies. Although bone deformities were never observed at any postnatal ages, minor and transient differences were noted in terms of bone length and static uCT parameters, but not systematically across all ages and genders. These changes, however, were not accompanied by significant alteration in bone material properties as assessed by a 3-point bending test. In addition, no changes were detected in circulating serum markers of bone turnover (P1NP, CTX-I, and osteocalcin). Gene expression monitoring also revealed no major impact of the loss of BRIL. Further, when mice were challenged with a surgically-induced fracture in tibia, bones repaired equally well in the KO mice as compared to WT. Finally, we showed that BRIL C-terminus is not a bona fide binding site for calcium. In conclusion, our in depth analysis suggest that skeletal patterning, bone mass accrual and remodeling in mice proceeded independent of BRIL.